2021
DOI: 10.1186/s13046-021-01895-w
|View full text |Cite
|
Sign up to set email alerts
|

Targeting AKT with costunolide suppresses the growth of colorectal cancer cells and induces apoptosis in vitro and in vivo

Abstract: Background Colorectal cancer (CRC) is a clinically challenging malignant tumor worldwide. As a natural product and sesquiterpene lactone, Costunolide (CTD) has been reported to possess anticancer activities. However, the regulation mechanism and precise target of this substance remain undiscovered in CRC. In this study, we found that CTD inhibited CRC cell proliferation in vitro and in vivo by targeting AKT. Methods Effects of CTD on colon cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 59 publications
(65 reference statements)
1
19
0
Order By: Relevance
“…Moreover, CTD represses hepatic fibrosis through the WW domain-containing protein-2-mediated Notch3 degradation and enhances the sensitivity of doxorubicin treatment to chronic myeloid leukemia cells through the PI3K/AKT pathway [ 40 , 41 ]. Our previous study also confirmed that CTD inhibited cell growth and triggered apoptosis through the MDM2/P53 pathway by targeting AKT in colon cancer [ 42 ]. Obviously, CTD is a potential inhibitor in cancer therapy.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, CTD represses hepatic fibrosis through the WW domain-containing protein-2-mediated Notch3 degradation and enhances the sensitivity of doxorubicin treatment to chronic myeloid leukemia cells through the PI3K/AKT pathway [ 40 , 41 ]. Our previous study also confirmed that CTD inhibited cell growth and triggered apoptosis through the MDM2/P53 pathway by targeting AKT in colon cancer [ 42 ]. Obviously, CTD is a potential inhibitor in cancer therapy.…”
Section: Discussionsupporting
confidence: 57%
“…Apart from that, recent results revealed that COS inhibited colorectal cancer cell proliferation and triggered apoptosis in vitro and in vivo by targeting the AKT-MDM2-p53 signaling pathway. Consequently, this compound was found to be worthy for further exploration in preclinical and clinical trials [ 287 ]. Moreover, COS has emerged as a potential tumor-specific candidate in skin cancer treatment.…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…24-well Transwell chambers (8 μm pore size; Corning, NY, United States) were used as published ( Huang H et al, 2021 ). For single-cell migration assessment, HFLS-RA cells (4 × 10 4 /well) in 200 μl serum-free medium were seeded in the upper chambers and treated with 20 µM celecoxib, umbelliferone, and scopoletin, respectively.…”
Section: Methodsmentioning
confidence: 99%